SMARTPHONE ADDICTION - Nikolic, Aleksandra M (HEALTH CARE, 2021)
The number of smartphone users worldwide exceeds three billion today and further growth of several hundred million is projected over the next few years. The development of multifunctional smartphones and their use have changed the way of communication and information, but also led to concerns about their excessive use and dependence. In recent years, research on smartphone addiction has been on the rise. Parallels between excessive smartphone use and behavioral addiction are common in research. According to many authors, "smartphone addiction" can be considered a behavioral addiction. There is evidence for structural and functional changes in the brain, characteristic of behavioral addictions, in people who meet the psychometric criteria for "smartphone addiction." Some authors even suggest criteria for diagnosing smartphone addiction. On the other hand, some authors believe that the use of the term "addiction" can misrepresent the severity of the disorder, and therefore suggest the use of the term "problematic smartphone use". Due to growing concerns about the excessive use of smartphones, much is being done to identify and assess problematic smartphone use, mainly through the development and application of behavioral assessment scales. These scales are specially developed and validated to identify problematic smartphone use or to diagnose people with smartphone addiction, overuse, excessive phone attachment, etc. However, despite the fact that most of these scales are designed to be used for clinical purposes in the future, the problematic use of smartphones as a type of addiction is not in the International Classification of Diseases and these scales are still used only for research purposes. The use of the terms " problematic smartphone use " and "smartphone addiction", different methodological approaches used in the study, such as the application of different scales and the lack of standardized diagnostic criteria, make it difficult to define "smartphone addiction". All this supports the fact that "smartphone addiction" is a complex phenomenon that requires additional research.
Keywords: addiction, smartphone, problemmatic samrtphone use